Tennis physiology: Training the competitive athlete - Kovacs, M. S. (Sports Medicine, 2007)
The game of tennis has evolved from the wooden-racket era of long, crafty points based on style and finesse, to the current fast paced, explosive sport based on power, strength and speed, where 210 km/h serves are common. This evolution over the last 20 years has led to an increased interest in tennis research. Competitive tennis athletes need a mixture of anaerobic skills, such as speed, agility and power, combined with high aerobic capabilities. The work-to-rest ratios of competitive tennis athletes range between 1 : 3 and 1 : 5, and fatigue has been shown to greatly reduce the hitting accuracy. Competitive male tennis athletes maintain body fat <12% and have maximal oxygen uptake values >50 mL/kg/min, and as high as 70 mL/kg/min. Results from lactate testing in tennis players are inconclusive as some studies have shown increased levels, whilst other studies have shown little or no change. Further investigation is required to determine the production and utilisation effects of lactate from playing tennis. The average length of time to play a point in tennis is <10 seconds and this has declined substantially in the last 20 years. Further research is needed to investigate tournament performance and its effect on fatigue, recovery, hormonal and injury levels. As the game of tennis continues to change, the physiological parameters must be continually investigated to help provide athletes, coaches and trainers with information that will aid in the development of efficient and productive tennis performance and injury prevention programmes.